Contemporary accounting : a conceptual approach - Jarvis, Robin; Bazley, Mike.; Hancock, Phil.; Berry, Aidan (South Melbourne : Nelson ITP, 1999)
This book is about: Introduction to accounting; The conceptual framework; The balance sheet; ...
Keywords: Accounting; Accounting -- Australia; Accounting -- AustraliaxProblems, exercises, etc; Accounting -- Study and teaching (Higher) -- Australia